EVALUASI PENGUKURAN KINERJA BALANCE SCORECARD PADA PERUSAHAAN (STUDI KASUS DI BPJS KETENAGAKERJAAN GRESIK) - Dian Anggraeni Riwanti; Suwarno Suwarno (PROCEEDING UMSURABAYA, 2022)
This study aims to determine the performance measurement of BPJS Ketenagakerjaan Gresik using the balanced scorecard method whether it can be said to be ideal as a whole from various perspectives. This study uses primary and secondary data. Primary data was obtained from interviews with informants and secondary data was obtained from reports on the achievement of performance realization in each perspective in 2015-2017. The case study used in this study is a single case study. The results of this study indicate that the balanced scorecard method cannot be applied optimally to BPJS Ketenagakerjaan Gresik because there are still perspectives whose realization has not yet reached the predetermined targets such as achievements in the financial perspective and the business and internal process perspective.Keywords: Performance Measurement; Balanced Scorecard.